Dexamethasone Stimulation Test in the Diagnostic Work-Up of Growth Hormone Deficiency in Childhood: Clinical Value and Comparison With Insulin-Induced Hypoglycemia - Cattoni, Alessandro; Molinari, Silvia; Medici, Francesco; De Lorenzo, Paola; Valsecchi, Maria Grazia; Masera, Nicoletta; Adavastro, Marta; Biondi, Andrea (Frontiers in Endocrinology, 2020)
Context: dexamethasone has been demonstrated to elicit GH secretion in adults, but few data are available about its effectiveness as a provocative stimulus in the diagnostic work-up of GH deficiency (GHD) in childhood. Objective: to assess the clinical value of dexamethasone stimulation test (DST) as a diagnostic tool for pediatric GHD. Design and setting: retrospective single-center analysis. The study population included 166 patients with a pathological response to arginine stimulation test (AST, first-line test) and subsequently tested with either insulin tolerance test (ITT) or DST as a second-line investigation between 2008 and 2019. Main outcome measures: comparison between GH peaks and secretory curves induced by ITT and DST; degree of agreement between DST and AST versus ITT and AST. Results: the pathological response to AST (GH peak <8 ng/mL) was confirmed by an ITT in 80.2% (89/111) of patients and by a DST in 76.4% (42/55), with no statistical difference between the two groups (p 0.69). Mean GH peaks achieved after ITT and DST were entirely comparable (6.59 ± 3.59 versus 6.50 ± 4.09 ng/ml respectively - p 0.97) and statistically higher than those elicited by arginine (p <0.01 for both), irrespectively of the average GH peaks recorded for each patient (Bland-Altman method). Dexamethasone elicited a longer lasting and later secretory response than AST and ITT. No side effects were recorded after DST. Conclusions: DST and ITT confirmed GHD in a superimposable percentage of patients with a pathological first-line test. DST and ITT share a similar secretagogue potency, overall greater than AST.